2020
DOI: 10.1111/pce.13861
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore‐induced DMNT catalyzed by CYP82D47 plays an important role in the induction of JA‐dependent herbivore resistance of neighboring tea plants

Abstract: Herbivore‐induced plant volatiles play important ecological roles in defense against stresses. However, if and which volatile(s) are involved in the plant–plant communication in response to herbivorous insects in tea plants remains unknown. Here, plant–plant communication experiments confirm that volatiles emitted from insects‐attacked tea plants can trigger plant resistance and reduce the risk of herbivore damage by inducing jasmonic acid (JA) accumulation in neighboring plants. The emission of six compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 56 publications
(87 reference statements)
3
59
0
Order By: Relevance
“…These plants are induced to synthesize the protease inhibitor and storage protein sporamin, which is toxic to chewing pests ( Meents et al, 2019 ). Similar results were also obtained in tea plants ( Camellia sinensis ) ( Jing et al, 2020 ). Gasmi and colleagues reported that exposure of Spodoptera exigua larva to herbivore-induced plant volatiles (HIPVs) such as indole increased its susceptibility to nucleopolyhedrovirus and Bacillus thuringiensis , and additionally they found that the microbiota population in larval midgut was significantly affected, but the mechanism remains unclear ( Gasmi et al, 2019 ).…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…These plants are induced to synthesize the protease inhibitor and storage protein sporamin, which is toxic to chewing pests ( Meents et al, 2019 ). Similar results were also obtained in tea plants ( Camellia sinensis ) ( Jing et al, 2020 ). Gasmi and colleagues reported that exposure of Spodoptera exigua larva to herbivore-induced plant volatiles (HIPVs) such as indole increased its susceptibility to nucleopolyhedrovirus and Bacillus thuringiensis , and additionally they found that the microbiota population in larval midgut was significantly affected, but the mechanism remains unclear ( Gasmi et al, 2019 ).…”
Section: Introductionsupporting
confidence: 82%
“…Another plant volatile indole was reported to show direct toxicity to insects, and it can regulate the balance between insects, their natural enemies, and host plants ( Veyrat et al, 2016 ; Ye et al, 2018 ). DMNT exists in various plant species, and different aspects of this compound have been studied, such as DMNT biosynthesis in plants, as well as that DMNT plays a role in signal transmission to neighbor plants after being attacked by insects ( Sohrabi et al, 2015 ; Richter et al, 2016 ; Liu et al, 2018 ), but these studies largely focused on its indirect role in plant protection ( Mumm et al, 2008 ; Li et al, 2018 ; Liu et al, 2018 ; Meents et al, 2019 ; Jing et al, 2020 ). Indeed, whether (and how) DMNT plays a direct role in killing pests has remained unknown until now.…”
Section: Discussionmentioning
confidence: 99%
“…The second major theme is the role of volatile signals in plant–plant communication, particularly in the context of defence against pathogens and herbivores. Frank et al (2021) demonstrate the potential importance of isoprene and β‐caryophyllene emissions in resistance priming against pathogens, while two papers show how indole (Ye et al, 2020) and 4,8‐dimethyl‐1,3,7‐nonatriene (DMNT) (Jing et al, 2020) emissions in tea plants lead to herbivore resistance. Finally, Moreira et al (2020) provide evidence that fungal pathogens may suppress volatile emissions in potato, to negate resistance priming in neighbouring plants.…”
mentioning
confidence: 99%
“…Compared to volatiles of unexposed tomato plant (Solanum lycopersicum L. [Solanaceae]), ZIPVs from tomato plant volatiles induced by the mirid predator Nesidiocoris tenus (Reuter) (Hemiptera: Miridae) were found to attract conspecific males and females (Rim et al, 2018) and the parasitoid Encarsia formosa Gahan (Hymenoptera: Aphelinidae) (Pérez-Hedo et al, 2015). Undamaged plants can also perceive HIPVs, OIPVs, ZIPVs, and herbivore pheromones as signals to mount defences against herbivores to the benefit of the host plant community (known as plant priming defences) (Figure 1) (Dicke and Bruin, 2001;Frost et al, 2008, Pérez-Hedo et al, 2015, but the priming defence is not observed in all plant species as reported for cotton plants exposed to pheromones (Magalhães et al, 2019) and tea plants exposed to the HIPV (E)-4,8-dimethyl-1,3,7-nonatriene (Jing et al, 2020).…”
Section: Chemical Interactions In Tri-trophic Systemsmentioning
confidence: 89%